1997
DOI: 10.1172/jci119547
|View full text |Cite
|
Sign up to set email alerts
|

A novel pancreatic endocrine tumor suppressor gene locus on chromosome 3p with clinical prognostic implications.

Abstract: The molecular pathogenesis of pancreatic endocrine tumors is largely unknown. Such tumors are more likely to develop in individuals with the von Hippel-Lindau (VHL) syndrome. We sought to determine whether allelic loss of the recently identified VHL tumor suppressor gene on chromosome 3p25-26 occurs in the more common sporadic forms of these tumors. Allelic loss on chromosome 3p was identified in 33% of 43 patients with endocrine tumors of the pancreas. The smallest common region of allelic loss, however, cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
73
2
5

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(92 citation statements)
references
References 41 publications
12
73
2
5
Order By: Relevance
“…18 -20 We found losses of 3p and 6pq and gains of 14q and Xq in association with an advanced disease stage, implying that these chromosomal regions may contain genes playing a role in tumor progression. Indeed, in previous studies 6,17 and the present one, allelic losses at 3p25 were found to be associated with clinically malignant EPTs, which might point to the location of a TSG. Furthermore, losses of 6q (see below) as well as gains of 14q and Xq have been reported to be involved in the progression of various other cancers.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…18 -20 We found losses of 3p and 6pq and gains of 14q and Xq in association with an advanced disease stage, implying that these chromosomal regions may contain genes playing a role in tumor progression. Indeed, in previous studies 6,17 and the present one, allelic losses at 3p25 were found to be associated with clinically malignant EPTs, which might point to the location of a TSG. Furthermore, losses of 6q (see below) as well as gains of 14q and Xq have been reported to be involved in the progression of various other cancers.…”
Section: Discussionsupporting
confidence: 62%
“…This locus has been postulated to harbor a novel EPT tumor suppressor gene (TSG). 6,17 Thus, microsatellite and FISH analysis confirmed the CGH data and, moreover, detected tetrasomy for chromosome 3 in one EPT and a microsatellite LOH of 3p25 in two tumors. This LOH was not detected with CGH, probably due to the small size of the chromosomal region lost (Ͻ10 Mb).…”
Section: Confirmation Of Cgh Datasupporting
confidence: 68%
See 1 more Smart Citation
“…This finding, however, was not confirmed in CGH and genome-wide allelotype studies (Speel et al 1999, Rigaud et al 2001. Allelic loss at 3p25 centromeric to the locus of the von Hippel-Lindau syndrome gene has been identified by Chung et al (1997) and found to be associated with malignancy. The association of 3p loss and metastatic disease was further supported by a CGH study of 44 tumours of different types (Speel et al 1999) and by a recent large study of 99 pancreatic endocrine tumours (Barghorn et al 2001a) with 3p LOH in 76.7% of metastasizing versus 41.5% of non-metastasizing tumours.…”
Section: Pancreasmentioning
confidence: 99%
“…Alguns estudos têm associado mutações genéticas ao grau de malignidade dos tumores de células beta. A perda de um alelo no cromossomo 3p é descrita em 57% dos tumores com extensão extra-pancreática enquanto a mesma alteração é encontrada em apenas 9% dos insulinomas restritos ao pâncreas (14). A perda de heterozigoze do gene p53 assim como a ativação de genes como o TGF alfa, myc e ras, são processos importantes na progressão do tumor (15).…”
Section: Discussionunclassified